1980
DOI: 10.1038/bjc.1980.246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of women with dysplasia or carcinoma in situ of the cervix uteri

Abstract: Summary.-To identify risk factors for various cervical abnormalities, 237 women with abnormal cervical smears and 422 control women were interviewed. Cervical biopsy specimens taken from the patients with abnormal smears were reviewed according to standard criteria by one pathologist and classified as follows: 65 carcinoma in situ, 81 severe dysplasia, 44 mild dysplasia and 47 normal histology. Factors associated with risk of mild dysplasia, severe dysplasia and carcinoma in situ were similar to those previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
3

Year Published

1983
1983
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(23 citation statements)
references
References 18 publications
1
19
0
3
Order By: Relevance
“…The relationship between cigarette smoking and apparent HPV infection has also been studied [Harris et al, 1980;Trevathan et al, 19831. The evidence for a positive relationship is not conclusive, but we, a t any rate, selected our samples from nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cigarette smoking and apparent HPV infection has also been studied [Harris et al, 1980;Trevathan et al, 19831. The evidence for a positive relationship is not conclusive, but we, a t any rate, selected our samples from nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that there was no control population who neither took the pill nor had the IUCD, making comparison with the background incidence of dysplasia or invasive cancer difficult. Harris et al (1980) (22) reported an increased risk of intraepithelial neoplasia with increasing duration of use for pill users. Ebeling et al (1987) (23) found that the risk of cervical cancer decreased after adjusting for sexual behavior and interval since last Pap smear but remained statistically significant or at borderline significance for long-term users of the pill (7þ years) and early onset users (< 24 years) with relative risks of 1.8 and 3.0, respectively.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…related to smoking, socioeconomic status and diet have also been proposed as causes of pre-malignant cervical disease (Brisson et al, 1988;Brock et al, 1989a, b;Cuzick et al, 1990;Guijon et al, 1985;Harris et al, 1980;Jones et a/., 1990;La Vecchia et al, 1986;Schneider and Shah, 1989;Trevathan et al, 1983).…”
mentioning
confidence: 99%